Proceedings of the FISITA 2012 World Automotive Congress Volume 11: Advanced Vehicle Manufacturing Technology. - SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Proceedings of the FISITA 2012 World Automotive Congress are selected from nearly 2,000 papers submitted to the 34th FISITA World Automotive Congress, which is held by Society of Automotive Engineers of China (SAE-China ) and the International Federation of Automotive Engineering Societies (FISITA). This proceedings focus on solutions for sustainable mobility in all areas of passenger car, truck and bus transportation. Volume 11: Advanced Vehicle Manufacturing Technology focuses on: •Applications of Aluminum, Magnesium and Zink Alloys , Composites •Advanced Body Manufacturing Technology •Body Corrosion Protection Technology •Welding, Joining and Fastening •Casting Technology •Stamping Technology •Paints, Polymers and Coatings •Exterior Body Panels •Advanced Process Management Above all researchers, professional engineers and graduates in fields of automotive engineering, mechanical engineering and electronic engineering will benefit from this book.   SAE-China is a national academic organization composed of enterprises and professionals who focus on research, design and education in the fields of automotive and related industries. FISITA is the umbrella organization for the national automotive societies in 37 countries around the world. It was founded in Paris in 1948 with the purpose of bringing engineers from around the world together in a spirit of cooperation to share ideas and advance the technological development of the automobile.
Applications of Aluminum, Magnesium and Zink Alloys, Composites -- Advanced Body Manufacturing Technology -- Welding, Joining and Fastening -- Stamping Technology -- Paints, Polymers and Coatings.-  Exterior Body Panels -- Advanced Process Management -- Other.
Keywords: Automotive engineering; Manufactures; Ceramics; Glass; Composites (Materials).; Composite materials; Automotive Engineering; Manufacturing, Machines, Tools, Processes; Ceramics, Glass, Composites, Natural Materials